Multi‐Mechanism Antibacterial Strategies Enabled by Synergistic Activity of Metal–Organic Framework‐Based Nanosystem for Infected Tissue Regeneration. Issue 14 (1st January 2023) - Xie, Wenjia; Chen, Junyu; Cheng, Xinting; Feng, Hao; Zhang, Xin; Zhu, Zhou; Dong, Shanshan; Wan, Qianbing; Pei, Xibo; Wang, Jian
Abstract: Drug‐resistant bacterial infection impairs tissue regeneration and is a challenging clinical problem. Metal–organic frameworks (MOFs)‐based photodynamic therapy (PDT) opens up a new era for antibiotic‐free infection treatment. However, the MOF‐based PDT normally encounters limited photon absorbance under visible light and notorious recombination of photogenerated holes and electrons, which significantly impede their applications. Herein, a MOFs‐based nanosystem (AgNPs@MOFs) with enhanced visible light response and charge carrier separation is developed by modifying MOFs with silver nanoparticles (AgNPs) to improve PDT efficiency. The AgNPs@MOFs with enhanced photodynamic performance under visible light irradiation mainly disrupt bacteria translation process and the metabolism of purine and pyrimidine. In addition, the introduction of AgNPs endows nanosystems with chemotherapy ability, which causes destructive effect on bacterial cell membrane, including membrane ATPase protein and fatty acids. AgNPs@MOFs show excellent synergistic drug‐resistant bacterial killing efficiency through multiple mechanisms, which further restrain bacterial resistance. In addition, biocompatible AgNPs@MOFs pose potential tissue regeneration ability in both Methicillin–resistant Staphylococcus aureus (MRSA)‐related soft and hard tissue infection. Overall, this study provides a promising perspective in the exploration of AgNPs@MOFs as nano antibacterial medicine against drug‐resistant bacteria for infected tissue regeneration in the future. Abstract : AgNPs@MOFs nanosystem with enhanced photodynamic performance under visible light mainly disrupts bacteria translation process, and the metabolism of purine and pyrimidine. AgNPs endow nanosystems with chemotherapy ability, which causes destructive effect on cell membrane, including membrane ATPase protein and fatty acid. AgNPs@MOFs nanosystem can perform as promising nano‐antibacterial medicine against drug‐resistant bacteria for infected tissue regeneration in the future.